VOLTAMMETRIC DETERMINATION OF PARACETAMOL WITH CARBON PASTE ELECTRODE MODIFIED WITH MOLECULARLY IMPRINTED ELECTROPOLYMER - WAYAN TANJUNG ARYASA (NIM : 20510003) ; Pembimbing : Dr. Indra Noviandri, I
Paracetamol (PCT) is a commom analgesic and antypyretic drug that is used for the relief of fever and headaches. The determination of paracetamol in pharmaceuticals is of very importance, becauce an overdose of paracetamol can cause fulminating hepatic necrosis and other toxic effects. Many analytical methodologies have been proposed for detrmination of paracetamol. The determinations are classified into five main categories: optical methods, electroanalytical methods, chromatographic methods, capillary electrophoretic methods and water analysis. Which one methode is to developed in the past two decades is electroanalytical methods in particularly for voltammetry method. In generally, voltammetry methode for analyses of paracetamol with uses modified electrode. In this study, developed for modified carbon paste electrode with molecularly imprinted polymer (MIP). Significant advantages to uses of MIP is superior stability, low cost and ease of preparation. The poly(3-aminiophenol) film was prepared by cyclic voltammetry method and 3-aminophenol monomer in supporting electrolyte (HClO4) with and whitout presence of paracetamol molecule. Effect of paracetamol was seen with simple at cyclic voltammogram is founded, where oxidation peak potential of poly(3-aminophenol) shifted to more cathodic potentials from 0.948 to 0.78 V, in presence of paracetamol. This oxidation peak indicates that the template is becoming part of the polymeric chain. The performance of the imprinted and non-imprinted polymer (NMIP) was evaluated by differential pulse voltammetry. Determination of important parameters to knows the performance for MIP electrode in detection the presence of paracetamol was insvestigated. Effect of the pH of the solution in oxidation of paracetamol at MIP electrode was studied with differential pulse voltammogram in buffer solution in the range pH 3-8. This indicates that paracetamol oxidation reaction of MIP electrode imfluence the pH of the paracetamol solution. The effect of scan rate on redoks peak currents of 1 mM paracetamol at the surface of in a phosphate buffer solution (pH 7) was studied. The cyclic voltammogram of paracetamol at range of scan rate is variation. The result reveal that confirms of occurs reversible process on paracetamol solution on surface of MIP electrode. Redox peak current of parcetamol showed the linear relationship when the scan rate is increased after the square root of the scan rate (u1/2) is indicate of the fact that diffusion controlled process for paracetamol electrooxidation. One of important parameter in this experiment is determination of calibrate plot for determine of detection limit of paracetamol. First range oncentration to taken at 0.2-4 mM but curve showed linearlity and correlation coefficient is not good. So that concentration range of paracetamol was reduce become concentrations range 0.01-0.1 mM (R2= 0.995), it show the linearity is very good. The detection limit (3 sigma) of paracetamol is 4.63 (mu)M. MIP electrode was made is selective for determination of paracetamol in presence of ascorbic acid. MIP electrode to give of potential response and peak current more good that NMIP electrode and carbon paste electrode. Analises result of drugs sample show accuration is very good with uses of voltammetry and spectrophotometry methods.